Clinical Evaluation of Assays for Plasma Renin Activity and Aldosterone Measurement by Liquid Chromatography–Tandem Mass Spectrometry. (30th November 2020) - Gibbons, Stephen M; Field, Helen P; Fairhurst, April; Fleming, Anne; Ford, Clive; Williams, Emma L; Barnes, Sophie C; Barth, Julian H
Abstract: Background: Aldosterone and renin are pivotal hormones in the regulation of salt and water homeostasis and blood pressure. Measurement of renin and aldosterone in serum/plasma is essential for the investigation of primary hyperaldosteronism (PA) and monitoring of glucocorticoid replacement therapy. Methods: We report 2 LC-MS/MS methods developed to measure aldosterone and plasma renin activity (PRA). PRA was determined by endogenous enzymatic generation of angiotensin I using 150 µL of sample. Generated angiotensin I was purified by solid phase extraction prior to chromatographic separation and mass spectrometry. Aldosterone measurement required 300 μL of sample extracted with MTBE prior to LC-MS/MS analysis. Results: The PRA method was linear (1.2–193 nmol/L), sensitive (LLOQ = 1.2 nmol/L), precise (CV = 4.1%), and specific (no cross reactivity for a number of structurally similar steroids). Dilutional linearity and recovery (84%) were acceptable. Accuracy was confirmed by comparison against our current RIA method. The aldosterone method had equally acceptable performance characteristics. Reference ranges in 110 healthy normotensive subjects were: PRA 0.2–3.7 nmol/L/h and aldosterone 50–950 pmol/L. Consecutive patients (n = 62) with adrenal incidentalomas shown to have no functional adrenal disease; their post overnight 1 mg dexamethasone test values were: PRA 0.2–2.6 nmol/L/h and aldosterone 55–480 pmol/L. Serum aldosterone values after 2 liter saline suppression were—normal subjects (n = 17): 78–238 pmol/L and confirmed primary hyperaldosteronism (n = 25): 131–1080 pmol/L. Conclusions: We have developed robust assays for PRA and aldosterone with appropriate clinical evaluation. These assays are now in routine practice in the UK.